Investigation of the relationship between smartphone addiction and overweight on university students (Annals of Medical Research, 2021)
Aim: Smartphone addiction and overweight are among the most important public health problems that are increasing day by day. However, to the best of our knowledge, there is no study investigating the relationship between these two health problems. The aim of this study was to investigate the relationship between smartphone addiction and overweight among university students.Material and Methods: The sample of this cross-sectional study consisted of 325 volunteers, 185 female and 140 male students. After the Smartphone Addiction Scale-Short Form (SAS-SF) and sociodemographic data form were applied to the volunteers, their height and weight were measured with the same device. Body Mass Index (BMI) was calculated and the sample was divided into normal weight (24.5 kg/m2 ≤ BMI ≤ 24.9 kg/m2) and overweight (BMI ≥ 25 kg/ m2).Results: The mean age of the volunteers included in the study was 22.38 ± 3.15 years and 56.9% (n = 185) of them were females. SAS-SF scores of the participants were found to be statistically different between normal and overweight groups (t=-2.524, p=0.012). According to the logistic regression analysis model used to determine the predictors of being overweight, being a smartphone addict increases the risk of being overweight twice. Conclusion: The study suggests that there is a relationship between smartphone use and being overweight. The results of our study are important since it is the first study that shows that smartphone addiction increases the risk of being overweight. In order to explain the relationship between these two important health problems, studies including other reasons of being overweight are needed.
Keywords: Smartphone addiction; obesity; overweight; body mass ındex; university student.